Description of a new pterygosomatid mite (Acari, Actinedida: Pterygosomatidae) parasitic on Liolaemus spp. (Iguania: Liolaemini) from Argentina - de La Cruz, Katharina Dittmar; Morando, Mariana; Avila, Luciano (Zootaxa, 2004)
Pterygosoma patagonica n. sp. (Acari: Pterygosomatidae) is described from endemic iguanid lizards (Liolaemus spp.) of Argentina, based on its morphology. This external parasite is also known to parasitize Old World agamid lizards.